Pheochromocytoma: present diagnosis and management. - Scott, H W (1976)
In the 25-year period 1950-1975 forty-four patients with pheochromocytoma were observed at Vanderbilt University Affiliated Hospitals. Bilateral adrenal tumors occurred in 3 patients (6.8%) and extra-adrenal tumors occurred in 7 others (16%), 33 patients (75%) had single tumors arising in one of the adrenal glands; in one of these 5 years after operation, a malignant tumor developed in the same renal fossa. Five of the 44 patients (11.3%) proved to have malignant tumors and died with metastases. In 11 patients in the earlier years of this study the clinical diagnosis was not made and the tumor was identified by the pathologist at autopsy. There was a single postoperative fatality among the 33 patients in whom the clinical diagnosis was made. Seventy per cent of all survivors with benign tumors have remained normotensive during followup periods of one to 20 years.